Mapping the educational experiences of children with pathological demand avoidance. Issue 4 (12th January 2015) - Gore Langton, Emma; Frederickson, Norah
Abstract : 'Pathological demand avoidance' (PDA) describes a pattern of difficulties increasingly recognised as forming part of the autistic spectrum. Although clinical reports suggest that children with PDA are likely to experience considerable difficulties in education, their educational experiences have not yet been explored in any systematic way. In the current study, 42 parents of children with PDA completed a questionnaire about their child's educational experiences. Parents' responses indicated that this group of children displays high levels of problem behaviours in school, and receives corresponding high levels of special educational need support and professional involvement. Despite this support, the group had experienced high rates of exclusion and placement breakdown, with only 48% now in mainstream education. Parents reported relatively high satisfaction in their children's educational placements, with success defined by parents in terms of child outcomes, school characteristics and PDA‐specific factors. Findings are discussed with reference to what is known about the educational experiences of children with more typical autism spectrum conditions and in terms of the implications for the inclusion of this group of children with complex needs.